A narrow linewidth terahertz dual-comb spectrometer with an all-fiber adaptive clock and a real-time feedback loop. (July 2023) - Xia, Yu; Li, Min; Liu, Zheng; Liu, Dikai; Bai, Songtao; He, Mingyang; Shen, Xuling; Yang, Kangwen; Yuan, Shuai; Yan, Ming; Huang, Kun; Zeng, Heping
Highlights: A broadband, mode-resolved terahertz comb spectrum is obtained with narrow linewidth. The adaptive-clock signal is obtained by all-fiber optical path and electronic signal processing. The real-time feedback loop with active frequency stabilization is used to realize the long-term stability of the system. Adaptive sampling effectively suppresses terahertz time-domain intensity jitter. Abstract: Terahertz comb spectroscopy offers advantages of high-resolution in broadband THz regions. However, conventional implementations of terahertz comb spectrometers are difficult to simultaneously achieve high precision and long-term stability due to the residual timing jitter of the involved light sources. In this work, an adaptive-clock signal from optical beat note in optical region was extracted for real-time correcting the unstable sampling interval-time caused by the residual timing jitter and a loosely active frequency-stabilized scheme functioned as a real-time feedback. And finally, a long-term stable terahertz dual-comb spectrometer was constructed with a spectral resolution of 66.14 MHz, a comb linewidth of 1.9 kHz, a fractional precision of 1.7 × 10 −9 and a long-term operation over 1200 h. This proved that the precise acquisition of THz pulses could be realized through the compensation of timing jitter for pumped optical pulses. The presented terahertz comb spectrometer is featured with enhanced robustness compared to previous schemes based on two fully stabilized mode-locked laser combs, which would thus facilitate field deployment outside the laboratories.